2017
DOI: 10.1016/s1473-3099(17)30359-6
|View full text |Cite
|
Sign up to set email alerts
|

Protection against cholera from killed whole-cell oral cholera vaccines: a systematic review and meta-analysis

Abstract: SummaryBackgroundKilled whole-cell oral cholera vaccines (kOCVs) are becoming a standard cholera control and prevention tool. However, vaccine efficacy and direct effectiveness estimates have varied, with differences in study design, location, follow-up duration, and vaccine composition posing challenges for public health decision making. We did a systematic review and meta-analysis to generate average estimates of kOCV efficacy and direct effectiveness from the available literature.MethodsFor this systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
162
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(174 citation statements)
references
References 37 publications
4
162
1
1
Order By: Relevance
“…Although kOCV with the B-subunit is less preferred for vaccine stockpile applications, our primary results present the kOCV efficacy profile with the B-subunit due to the biological plausibility of the estimates in the time-varying analysis [22] and the recent observation that two-dose vaccine efficacy with and without the B-subunit is likely indistinguishable. [23] Though in reality many other forces likely contributed to the Bentiu PoC Camp's susceptibility to the observed cholera outbreak, our case study shows that known key drivers (namely waning vaccine efficacy, a net influx of susceptible people through population mobility) alone are strong enough to produce the observation that the camp population sustained a cholera outbreak despite recent vaccination campaigns. Provided additional data on the cholera outbreak and the camp population, a complete cholera model fit to the epidemic may yield additional insights.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Although kOCV with the B-subunit is less preferred for vaccine stockpile applications, our primary results present the kOCV efficacy profile with the B-subunit due to the biological plausibility of the estimates in the time-varying analysis [22] and the recent observation that two-dose vaccine efficacy with and without the B-subunit is likely indistinguishable. [23] Though in reality many other forces likely contributed to the Bentiu PoC Camp's susceptibility to the observed cholera outbreak, our case study shows that known key drivers (namely waning vaccine efficacy, a net influx of susceptible people through population mobility) alone are strong enough to produce the observation that the camp population sustained a cholera outbreak despite recent vaccination campaigns. Provided additional data on the cholera outbreak and the camp population, a complete cholera model fit to the epidemic may yield additional insights.…”
Section: Discussionmentioning
confidence: 77%
“…Cholera vaccine efficacy has been shown to vary by age of recipient, [22,23,27] however for simplicity and lack of detailed data we do not model this age structure. If children respond poorly to kOCV and are members of a mass vaccination campaign, we would expect herd immunity to wane more quickly, and especially so if children are disproportionate sources of transmission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to successful campaigns conducted in over 15 countries since 2013 [5], countries that regularly experience cholera are beginning to integrate vaccination with oral cholera vaccine (OCV) into regular public health activities, as recommended by the Global Task Force on Cholera Control (GTFCC) Roadmap to 2030 and general WHO guidance [6]. These vaccines have 49-67% efficacy in protecting vaccine recipients against cholera infection for up to five years [7], thus presenting an important near-term solution to rapidly reducing cholera risk while long-term improvements to safely managed and sustainable water and sanitation services are made. Moreover, killed whole-cell cholera vaccines are known to be very safe; trials for vaccines currently included in WHO stockpiles have not found evidence for vaccine-related adverse events in non-pregnant or pregnant populations [8,9].…”
Section: Introductionmentioning
confidence: 99%